Coronary microvascular function is impaired in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy. (31st December 2020) - Argirò, Alessia; Sciagrà, Roberto; Marchi, Alberto; Beltrami, Matteo; Spinelli, Enrico; Salvadori, Emilia; Bianchi, Andrea; Mascalchi, Mario; Poggesi, Anna; Olivotto, Iacopo; Pescini, Francesca
Abstract: Background and purpose: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a rare inherited disease caused by NOTCH3 gene mutations. Although the main clinical features reflect brain injury, CADASIL is a systemic microangiopathy, and cardiac involvement has been observed but not systematically assessed. We aimed to study the prevalence and severity of coronary microvascular dysfunction (CMD) in CADASIL patients. Methods: Seventeen patients with genetically confirmed CADASIL, aged <60 years (mean age 40 ± 9 years), with ≤1 cardiovascular risk factor underwent neurological and neuropsychological evaluation, 3T brain magnetic resonance imaging (MRI), 12‐lead electrocardiography (ECG), standard echocardiography, and measurement of myocardial blood flow at rest (resting MBF) and of maximal myocardial blood flow following Regadenoson infusion (Reg‐MBF) by 13 NH3 positron emission tomography (PET). Coronary flow reserve (CFR) was defined as Reg‐MBF/resting MBF. PET results were compared to those of 15 healthy controls who were age and sex matched. Results: Twelve patients (71%) presented migraine, none (53%) had psychiatric disturbances, and one (6%) had a previous stroke. None had cognitive impairment or ECG or echocardiography abnormalities. Both Reg‐MBF and CFR were blunted in CADASIL patients compared with controls (Reg‐MBF 2.46 ± 0.54 vs. 3.09 ± 0.44 ml/g/min, respectively; p  < 0.01; CFR 2.74 ± 0.36 vs. 3.28 ± 0.66, respectively, p  < 0.01). No correlations were found between Reg‐MBF values and neuropsychological performance or cerebral lesion burden on MRI. Conclusions: CADASIL patients exhibit blunted CFR due to CMD, which can be severe and is independent of the severity of brain lesion load and cognitive performances. CADASIL is a systemic microcirculation disease, and active surveillance of cardiac symptoms should be considered in these patients. Abstract : Coronary microvascular function is blunted in CADASIL patients.